Industrial case study of aerial systems using ray-tracing and antenna optimisation - Mohanta, Krishnakanth; Al-Rubaye, Saba; Tsourdos, Antonios (Institute of Electrical and Electronics Engineers (IEEE), 2026)
An industrial case study of Unmanned Aerial System (UAS) operation and communications for integrated satellite-terrestrial networks in remote regions is considered. The objective is to evaluate and optimize the Quality of Service (QoS) of communication networks that combine satellite backhaul and ground-based transmission infrastructure for UAS operations. To address this challenge, this paper proposes a new algorithm for antenna tilt optimization procedure aiming to enhance terrestrial coverage, and maximise average Received Signal Strength Indicator (RSSI) along predefined UAS paths using terrain-aware ray-tracing models. A preliminary analysis of the satellite link is performed using simulation-based model of phased array terminal, assessing its suitability for Beyond Visual Line of Sight (BVLOS) operations through latency and RSSI profiling under variable link conditions. In addition, the study quantifies the QoS of the terrestrial network by analyzing RSSI, Signal-to-Interference-plus-Noise Ratio (SINR), latency, and throughput across UAS routes between key islands. The findings highlight the effectiveness of hybrid satellite-terrestrial architectures in extending coverage and reliability for critical UAS operations in geographically challenging environments. This work informs future network planning strategies for remote UAS deployments.
Keywords: 46 Information and Computing Sciences; 4006 Communications Engineering; 40 Engineering; 4008 Electrical Engineering; UAV Communications; Satellite-Terrestrial Integration; Quality of Service (QoS); Ray-Tracing Propagation Modelling; Antenna Optimisation